2020
DOI: 10.7717/peerj.7905
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth-promoting rhizobacteria on co-inoculation with Bradyrhizobium in soybean crop: a meta-analysis of studies from 1987 to 2018

Abstract: Background The co-inoculation of soybean with Bradyrhizobium and other plant growth-promoting rhizobacteria (PGPR) is considered a promising technology. However, there has been little quantitative analysis of the effects of this technique on yield variables. In this context, the present study aiming to provide a quantification of the effects of the co-inoculation of Bradyrhizobium and PGPR on the soybean crop using a meta-analysis approach. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 57 publications
4
44
0
1
Order By: Relevance
“…About 98% of soybean meal is used for making aquaculture and livestock feeds due to higher protein contents (38-44%). Industrial uses of soybean oil include the manufacturing of printing inks, soaps, insecticides, paints, linoleum, and disinfectants [2].…”
Section: Introductionmentioning
confidence: 99%
“…About 98% of soybean meal is used for making aquaculture and livestock feeds due to higher protein contents (38-44%). Industrial uses of soybean oil include the manufacturing of printing inks, soaps, insecticides, paints, linoleum, and disinfectants [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 ), at least in A. thaliana , is not surprising as several members of the Cupriavidus genus and the Burkholderiaceae family are well-known PGPRs or, at least, interact with plants ( Gyaneshwar et al, 2011 ; Bhattacharyya & Jha, 2012 ; Poupin et al, 2013 ; Arroyo-Herrera et al, 2020 ). Because PGPR traits ( Zeffa et al, 2020 ), including 1-aminocyclopropane-1-carboxylate deaminase, auxin phytohormone production, phosphate solubilization, and nitrogen fixation ( Bhattacharyya & Jha, 2012 ; Aeron et al, 2020 ), have not yet been reported in C. metallidurans , new PGPR traits would be interesting to explore in this bacterium. New PGPR traits could emerge from further in-depth study of the responses that gobernate this interkingdom relationships.…”
Section: Discussionmentioning
confidence: 99%
“…PGPR are the soil bacteria that colonize the roots of the plants and aid the plant growth. Their role in plant growth nutrient management and biocontrol activity is very well established (Rincón‐Molina et al, 2020; Yasmin et al, 2020; Zeffa et al, 2020). PGPR alter plant defense response under drought by modifying morphological, biochemical, and genetic responses of maize plants (García et al, 2017; Yasmin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%